COVID-19 vaccination refusal trends in Kenya over 2021. Issue 5 (27th January 2023) - Rego, Ryan T.; Kenney, Brooke; Ngugi, Anthony K.; Espira, Leon; Orwa, James; Siwo, Geoffrey H.; Sefa, Christabel; Shah, Jasmit; Weinheimer-Haus, Eileen; Sophie Delius, Antonia Johanna; Pape, Utz Johann; Irfan, Furqan B.; et al.
Abstract: Background: Vaccination refusal exacerbates global COVID-19 vaccination inequities. No studies in East Africa have examined temporal trends in vaccination refusal, precluding addressing refusal. We assessed vaccine refusal over time in Kenya, and characterized factors associated with changes in vaccination refusal. Methods: We analyzed data from the Kenya Rapid Response Phone Survey (RRPS), a household cohort survey representative of the Kenyan population including refugees. Vaccination refusal (defined as the respondent stating they would not receive the vaccine if offered to them at no cost) was measured in February and October 2021. Proportions of vaccination refusal were plotted over time. We analyzed factors in vaccination refusal using a weighted multivariable logistic regression including interactions for time. Findings: Among 11, 569 households, vaccination refusal in Kenya decreased from 24 % in February 2021 to 9 % in October 2021. Vaccination refusal was associated with having education beyond the primary level (−4.1[−0.7, −8.9] percentage point difference (ppd)); living with somebody who had symptoms of COVID-19 in the past 14 days (−13.72[−8.9, −18.6]ppd); having symptoms of COVID-19 in the past 14 days (11.0[5.1, 16.9]ppd); and distrusting the government in responding to COVID-19 (14.7[7.1, 22.4]ppd). There were significant interactions with time and: refugee status and geography, living with somebody with symptoms of COVID-19, having symptoms of COVID-19, and believing in misinformation. Interpretation: The temporal reduction in vaccination refusal in Kenya likely represents substantial strides by the Kenyan vaccination program and possible learnt lessons which require examination. Going forward, there are still several groups which need specific targeting to decrease vaccination refusal and improve vaccination equity, including those with lower levels of education, those with recent COVID-19 symptoms, those who do not practice personal COVID-19 mitigation measures, refugees in urban settings, and those who do not trust the government. Policy and program should focus on decreasing vaccination refusal in these populations, and research focus on understanding barriers and motivators for vaccination.